1998
DOI: 10.1002/pro.5560070503
|View full text |Cite
|
Sign up to set email alerts
|

Motifs and structural fold of the cofactor binding site of human glutamate decarboxylase

Abstract: The pyridoxal-P binding sites of the two isoforms of human glutamate decarboxylase (GAD65 and GAD67) were modeled by using PROBE (a recently developed algorithm for multiple sequence alignment and database searching) to align the primary sequence of GAD with pyridoxal-P binding proteins of known structure. GAD'S cofactor binding site is particularly interesting because GAD activity in the brain is controlled in part by a regulated interconversion of the apo-and holoenzymes. PROBE identified six motifs shared b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

1999
1999
2005
2005

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 38 publications
0
23
0
1
Order By: Relevance
“…These studies, and a statistical analysis of alignment data (15) indicated that the active site of GAD is in a fold formed by the interaction of two GAD monomers and that the interaction does not depend on disulfide bonds, but is instead due to some other interaction between the C-terminal domains of the two interacting monomers. This information is in accord with previous findings that GAD must be a dimer to be active and that it can consist of homodimers of either isoform, or as heterodimers formed from monomers of the two types (16).…”
Section: Introductionmentioning
confidence: 94%
“…These studies, and a statistical analysis of alignment data (15) indicated that the active site of GAD is in a fold formed by the interaction of two GAD monomers and that the interaction does not depend on disulfide bonds, but is instead due to some other interaction between the C-terminal domains of the two interacting monomers. This information is in accord with previous findings that GAD must be a dimer to be active and that it can consist of homodimers of either isoform, or as heterodimers formed from monomers of the two types (16).…”
Section: Introductionmentioning
confidence: 94%
“…The sequence of the Ab-binding peptides identifies amino acids critical for binding. The second is sequence alignment and secondary structure prediction of PLP-dependent decarboxylases and aminotransferases, which have shown that the PLP binding domain of ornithine decarboxylase (OrnDC) and aspartate aminotransferase from bacteria share a protein fold that is common to other PLPdependant proteins, including GAD65 (25,26). This has enabled the derivation of structural models of the GAD PLP binding domain (27), and such models can be used to formulate specific hypotheses regarding epitope structure.…”
Section: G Lutamic Acid Decarboxylase (Gad)mentioning
confidence: 99%
“…Homo-and Heterodimerization of GAD65 Does Not Involve the NH 2 -terminal Membrane-anchoring Region-Molecular modeling studies have suggested that the middle domain of each subunit is involved in GAD65 dimerization (16,17). Since there are no proteins of known structure that share sequence homology with GAD65 in the first 100 amino acids at the NH 2 terminus of GAD65 (16), a structure prediction is not available for this region.…”
Section: Targeting To Nerve Terminals and Membrane Anchoringmentioning
confidence: 99%
“…The results presented here show that the GAD65⌬1-101 mutant is exclusively detected as a dimer in nondenaturing gels and therefore provide the first evidence that the NH 2 -terminal region of GAD65 is not important for homodimerization. Thus, the predicted interactions of several residues in the middle domain of one subunit with PLP in the active site of the second subunit may represent the main bonds between the subunits (17).…”
Section: Targeting To Nerve Terminals and Membrane Anchoringmentioning
confidence: 99%
See 1 more Smart Citation